2007
DOI: 10.1111/j.1365-2796.2007.01849.x
|View full text |Cite
|
Sign up to set email alerts
|

Retinol‐binding protein 4 as a plasma biomarker of renal dysfunction and cardiovascular disease in type 2 diabetes

Abstract: Objective. The retinol-binding protein 4 (RBP4) has been linked to the insulin resistance state in obesity and type 2 diabetes in animal studies. Data in humans are controversial and their relationship with organ damage in diabetic patients is lacking. We studied the association of plasma RBP4 with organ complications in type 2 diabetic patients.Setting. Sant Joan University Hospital, Reus, Spain.Subjects. 165 nonsmoker type 2 diabetic subjects according to American Diabetes Association criteria, aged 36-79 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
101
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(108 citation statements)
references
References 25 publications
(33 reference statements)
4
101
2
1
Order By: Relevance
“…Increased serum RBP4 levels are reportedly associated with body mass index, waist circumference, and insulin resistance (Yang et al, 2005;Graham et al, 2006;Cabré et al, 2007). We observed that serum RBP4 concentrations decreased rapidly as early as 1 day after kidney transplantation.…”
Section: Discussionmentioning
confidence: 53%
“…Increased serum RBP4 levels are reportedly associated with body mass index, waist circumference, and insulin resistance (Yang et al, 2005;Graham et al, 2006;Cabré et al, 2007). We observed that serum RBP4 concentrations decreased rapidly as early as 1 day after kidney transplantation.…”
Section: Discussionmentioning
confidence: 53%
“…However, there are several controversial results regarding insulin resistance [8][9][10][11][12][13]. In diabetic nephropathy plasma RBP4 levels are further elevated in diabetic subjects with microalbuminuria [14][15][16].…”
mentioning
confidence: 99%
“…Among them, there was significant deviation of five proteins [β-2-microglobulin, annexin A1, complement C5, retinol-binding protein 4 (RBP4) and argininosuccinate synthase], which are known to potentially participate in IgAN and certain glomerular diseases (15)(16)(17)(18). The present study provides additional evidence that iTRAQ technology accurately quantifies the relative changes in the protein abundance of renal tissue.…”
Section: Discussionmentioning
confidence: 68%